Contatto tra i componenti di una protesi di ginocchio: studio numerico e sperimentale - D. Tumino; M. Saporito; L. D’Acquisto; T. Ingrassia; D. Cerniglia (Fracture and Structural Integrity)
The aim of this work is the analysis of the contact area in a knee prosthesis using two different approaches. In particular, the interface between the femoral component and the polyethylene insert has been studied both numerically and experimentally. The interest in studying the contact area is related to the fact that the wear of the polyethylene insert, due to the high contact pressures, represents one of the major causes of failure of the total knee prosthesis. The possibility to evaluate the contact area at different loads and mutual position between femur and tibia is, therefore, of fundamental importance to study the service life of a prosthesis and to improve its performance. The finite element numerical approach has required the acquisition, through reverse engineering, and CAD modelling of the prosthetic components. Then the FEM simulations have been developed considering two different load conditions. In order to compare the calculated data, the same load configurations have been used for experimental tests based on ultrasonic method. In this case, some preliminary tests were required to calibrate the system depending on the particular characteristics of materials, geometries and surface finish of the prosthesis.The results show a good correlation between the data obtained with the two different approaches and, consequently, a good level of reliability of the procedures developed for the numerical and experimental evaluation of the contact area. The numerical procedure can be used to determine the area for different angles and loads, but especially in the design phase. The ultrasonic technique can be used to validate the numerical data.